SISTEM INFORMASI PANTI ASUHAN TAMAN BINA INSANY BERBASIS WEB: Orphanage;Information System;R&D;Sublime Text;Phpmyadmin. - Louis, Ahmad; Suryani, Nike Ade (FORTECH (Journal of Information Technology), 2022)
Taman Bina Insany is one of the orphanages whose information system is still done manually, so that the dissemination of information and the data storage process is considered to be less effective and efficient. This causes this orphanage to be unknown to many people as well as the emergence of problems in data processing such as the occurrence of file loss or accumulation. For this reason, research was carried out to design a new website-based system. The research method used in this research is the R&D (Research and Development) method, with applications and programming languages ​​using Sublime Text and PHPMyAdmin. In this information system there is input in the form of orphanage data such as foster children data, management data, galleries, activities, and the donation process which will be displayed in the form of output in the form of reports. It is hoped that this website can facilitate the process of disseminating information so that it can be accessed more widely and makes it easier for administrators to manage data.